KONSTRUKSI MAKNA MINORITAS DALAM INTERAKSI SOSIAL MAHASISWA ETNIS TIONGHOA DI UNIVERSITAS BUDI LUHUR DAN UNIVERSITAS BINA NUSANTARA - Ni Gusti Ayu Ketut Kurniasari (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2018)
In its development, the existence of ethnic Indonesians Chinese descent is inseparable from the development of governmental system in the Country. Since the New Order era, the eth-nic members have been playing pivotal role in economic realm. However a significant de-velopment occurred during the era of Abdurrahman Wahid administration that allowed access for Indonesians Chinese to attend school or study in public universities. Since then, educational institutions in Indonesia have been accommodated multiculturalism by recog-nising the existence of various ethnics in Indonesia, although the term of minority for cer-tain ethnics still become problem and inherent identity. Therefore, this research raised the title; Construction meaning of minority in social interaction of Chinese Indonesian students at Universitas Budi Luhur and Universitas Bina Nusantara. The problem formulation in this research is: How purport identity ethnic minority Chinese students in social interaction at the Universitas Budi Luhur and Universitas Bina Nusantara? How does social interac-tion performed by students of Chinese ethnicity at Universitas Budi Luhur and Universitas Bina Nusantara? This study also uses the theory of identity and theory phenomenology by George Herbert Mead. But as a result of this research was the meaning/significance of Indonesian Chinese minority identity is strongly linked with social interaction occurred. The awareness to boldly preserve and display Ethnic's culture and traditions begins in families. This serves as guidelines to determine how to behave and interact within the community of Indonesians Chinese and within university life. Social interaction within the ethnic group is varied depending on religious beliefs, languages, and cultural stereotypes have become distinguishing factors of social interaction process.